Diksi dan Majas dalam Antologi Puisi Sajak Sang Cendekia Karya Guru MAN Insan Cendekia - Sukainah, Sukainah; Afryansyah, Afryansyah; Marlisah, Marlisah (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The form of the author's imagination and ideas that are present due to personal experiences that occur around the author's environment is called poetry. The selection of the poetry anthology of Sajak Sang Cendekia by MAN Insan Cendekia teachers was based on brief findings that were seen in terms of diction and figure of speech which were interesting to be studied further using stylistic studies. This study uses stylistics which is focused on the theory of diction and figure of speech. The stylistic approach is carried out by analyzing diction, figure of speech and its function in an anthology of poetry Sang Cendekia by the teachers of MAN Insan Cendekia. The source of the data is in the form of an anthology of Poetry Sajak Sang Cendekia written by MAN Insan Cendekia teachers throughout Indonesia. The poetry anthology consists of 121 poems which were first printed in April 2021 and published by CV Kanaka Media with 188 pages thick. The anthology of Poetry Sajak Sang Cendekia was created as a form of appreciation for Indonesian MGMP teachers at MAN IC in Indonesia. This anthology of The Scholar's Poems is a manifestation of the work of the first Indonesian language teacher MAN Insan Cendekia, during the Covid-19 outbreak in order to open the door of imagination to become a well-packaged and attractive theme choice. The data analysis technique used was descriptive qualitative analysis technique. ABSTRAK: Bentuk dari hasil imajinasi dan ide pikiran pengarang yang hadir karena pengalaman pribadi yang terjadi di sekitar lingkungan pengarang disebut dengan puisi. Pemilihan antologi puisi Sajak Sang Cendekia karya guru-guru MAN Insan Cendekia didasarkan pada temuan sekilas yang dilihat dari segi diksi dan majas yang menarik untuk dikaji lebih jauh dengan menggunakan kajian stilistika. Penelitian ini menggunakan stilistika yang difokuskan pada teori diksi dan majas. Pendekatan stilistika dilakukan dengan cara menganalisis diksi, majas dan fungsinya dala sebuah antologi puisi Sajak Sang Cendekia karya Guru-guru MAN Insan Cendekia. Adapun sumber datanya berupa antologi puisi Sajak Sang Cendekia yang ditulis oleh Guru-guru MAN Insan Cendekia se-Indonesia. Antologi puisi tersebut terdiri atas 121 puisi yang dicetak pertama kalinya pada bulan April tahun 2021 dan diterbitkan oleh CV Kanaka Media dengan tebal 188 halaman. Antologi puisi Sajak Sang Cendekia dibuat sebagai bentuk apresiasi guru MGMP Bahasa Indonesia MAN IC se-Indonesia. Antologi Sajak Sang Cendekia ini sebagai wujud karya guru Bahasa Indonesia MAN Insan Cendekia yang perdana, pada masa wabah Covid-19 agar dapat membuka pintu imajinasi untuk menjadi pilihan tema yang dikemas baik dan menarik. Adapun, teknik analisis data yang digunakan adalah teknik analisis deskriptif kualitatif.